Aspects Regarding the Workforce Resources in Bihor County (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
The purpose of this paper is to analyze labor resources in Bihor County and to highlight some of aspects that characterize the current condition of this population category. In this respect, the paper reveals that the population is found in a process of demographic aging, with negative implications upon the utilization of workforce. Based on analysis of statistical data provided by the statistical yearbook, the paper result show that the workforce renewal rate in Bihor County is in deficit, respectively 100 individuals turned inactive, are replaced by only 79 individuals, who come under the category of the active population. Furthermore, the fact that the active civilian population represents only 66,9 % of the overall potential active population, emphasizes a relatively feeble use of the workforce. Finally, the paper reveals a significant numeric decrease, during the past years, of the individuals activating within the healthcare and social work departments. Thus, this decrease has a negative consequence upon the health condition of the population.